Shenipabu Miyui: literatura e mito - Guesse, Érika Bergamasco [UNESP] (2014)
Due to the potential indigenous contribution to the Brazil’s cultural and literary scene and considering the scarcity of academic studies about narrative comprehension and poetic creations that have the Brazilian Indian as author / creator, the current research contains an analysis of a group of twelve narratives, included in Shenipaby Miyui, gathered between 1989 and 1955.The narratives are authored by the Kaxinawá Indians - given that they come from oral tradition - and the volume was organized by the indigenous teacher Joaquim Mana Kaxinawá.The mythical narratives that compose this work were narrated in versions both in the indigenous language Kaxinawá and in the Portuguese language and were, in this case, told by Indians that mastered the white people’s language.The current research works with only the ones that were told by the Indians themselves in Portuguese.This work basically encompasses three topics: a) discussion about the configuration, in Brazil, of what we can call author indigenous literature; b) myth study, aiming specially at its characteristics as literary and cultural matter, focusing on indigenous myths, that go through a process of migration of orality to writing, in order to help conserve its stories and habits; c) analysis of mythical narratives, composed in Portuguese, of Shenipabu Miyui, considering these texts as literary or aesthetic works; showing, in the stories, how the integrative vision of the world (kaxinawá) happens, mainly through strongly present metamorphoses ; and analyzing the protagonist’s trajectory, thus showing the similarities and specificities of these texts in relation to other popular narratives